Spontaneous infarction of superficial lymph nodes - Davies, J. Douglas (1972)
Five cases of extensive infarction of lymph nodes were traced in just over 16 years' surgical material. All presented with painful swelling in a superficial lymph node chain. None was diagnosed clinically; two were interpreted as fibroadenoma of the axillary tail of the breast, and two as a femoral hernia. Microscopically the lymph nodes in the first three weeks after infarction were characterized by extensive necrosis of medullary and cortical lymphoid cells, but the central reticulin architecture and a narrow, incomplete rim of viable subcapsular lymphoid tissue were preserved. Reactive perinodal inflammation and the formation of granulation tissue resembled the reaction to myocardial infarction. The late stage of the lesion was characterized by incomplete regeneration of lymphoid tissue in the lymph nodes. The lesions appeared attributable to thrombosis of veins within the substance and the hila of the nodes.